A return to prioritizing needs: Adaptation or mitigation alternatives?. (October 2014) - Al-Amin, Abul Quasem; Filho, Walter Leal
This study empirically explores climate change-related impacts on rice farming by using global circulation models together with crop modelling. The approach uses a bottom-up strategy which focuses on agricultural production loss under various climatic conditions following observational records of precipitation and warming climatic factors up to the year 2090. The study provides a wide range of potential climate outcomes and assesses the comparative advantages of both mitigation and adaptation alternatives concerning prioritizing requirements to reduce scenario vulnerabilities in rice agriculture. Utilizing scenario vulnerabilities, this study visualizes alternative guidelines and some of the potential paths policymakers could take with their planning strategies. The issue considered in the present study could be used as a reference for developing climate change and global warming-related agricultural policies in Malaysia and other places with similar ecological conditions.